Corporate social responsibility in India - "Panda, Sanjay Kumar" (New Delhi, 2018)
This book has outlined steps to be taken by the major stakeholders - the Corporate, the Government and the Civil society- for making CSR effective in the Indian context.
Keywords: Corporate social responsibility - India